Pengembangan dan Penerapan Sistem Informasi Marketplace UMKM - Yohana Dewi Lulu Widyasari; Abiyyu Taufiq Ramadhan (Politeknik Caltex Riau, 2022)
The Indonesian people in improving their economy form a business or business entity on their own initiative. In many areas, MSMEs use natural resources that have the potential. MSMEs are a means to create new jobs and can be an alternative in reducing the number of unemployed. Currently, the main problem for MSME actors is the existence of obstacles in selling their products widely so that it has an impact on the lack of effectiveness and efficiency of the sales process carried out. Another problem is the lack of information to the public about MSMEs and MSME products that are currently being sold. Based on the problems, an MSME Marketplace information system was built which can be a medium for buying and selling MSME products online. every MSME that has registered on the marketplace can manage their own MSMEs. Marketplace owners can have a system that can record MSMEs. This system was created using the Hypertext Processor (PHP) programming language and MqSQL database. System development is done using the prototyping method in 3 iterations. The results of the prototyping iteration have been implemented well in the system development. The results of black box testing stated that this system was running properly. UAT results in 95% to assess this system has functionality that runs well, and whether users have been able to accept the system.